Hubungan kemahiran berfikir aras tinggi dan metakognitif terhadap pengajaran secara kerja buat dalam kalangan guru sains sekolah rendah di Jempol, Malaysia - Subramaniam, Punnithann (2018)
Higher order thinking skills and metacognitive skills are essential skills in generating intellectual competitiveness generation to meet the challenges of acquiring today's knowledge. The commitment to promote higher order thinking skills has become a major agenda of quality education in Malaysia. This study examine the relationship between higher order thinking skills (HOTS) and metacognitive towards science hands-on teaching among primary school science teachers in Jempol district. The purpose of this study is to observe the relationship between the level of higher order thinking skills (HOTS) and metacognitive skills towards science hands-on teaching among the primary school science teachers in Jempol district. The design of this study is descriptive method and inferential. This study uses quantitative approach by using questionnaire. The data analysis used were descriptive statistics, Pearson correlation test and multiple regression analysis. The total population of Jempol district science teachers is 135 teachers and 108 samples have been selected for this study. The findings of analysis showed that the level of teachers' thinking skills is high (M = 4.36, S.D.= 0.577) among science teachers in Jempol district. In addition, the findings show that the metacognitive level was high (M = 4.39, S.D. = 0.579) among science teachers in Jempol district. Next, the level of science hands-on teaching is high (M = 4.37, S.P. = 0.543) among the science teachers in this district. This clearly shows that teachers in this area practices predicting skills, constructing hypothesis, experimenting and making inference during science hands-on teaching. The findings show that there is a significant relationship between higher order thinking skills (HOTS) and science hands-on teaching (r =0.739, n = 94, p <0.01). In addition, the findings show that there is a significant relationship between metacognitive and science hands-on teaching (r=0.826, n=94, p<0.01). The level of metacognitive relationship is stronger than the higher order thinking skills (HOTS). The r value of metacognitive is (r = 0.826) and the r value of the higher order thinking skills (HOTS) is (0.739). Multiple regression analysis was conducted and the findings showed the Beta value for metacognitive is higher (0.626) compared to the Beta value of higher order thinking skills (HOTS) (0.265). This study will have an impact on science teachers in the Jempol district to focus more on higher order thinking skills and metacognitive teaching in the workplace. A teacher should practice higher order thinking skills and metacognitive skills in a consistent manner in teaching science. This directly addresses the needs of the 21st century educational environment.